Odpowiedź:
zad 1
3x- 1/3y = 2 | * 3
- 9x + 7y = 12
9x - y = 6
- 9x + 7y = 12
dodajemy równania
9x -9x - y + 7y = 6 + 12
6y = 18
y = 18/6 = 3
9x - y = 6
9x - 3 = 6
9x = 6 + 3 = 9
x = 9/9 = 1
zad 2
(x - 1)/2 + (y + 1)/3 = 3 | * 6
(x + 1)/3 - (y- 2)/6=2 | * 6
3(x - 1) + 2(y + 1)= 18
2(x + 1) - y + 2 = 12
3x - 3 + 2y + 2 = 18
2x + 2 - y + 2 = 12
3x + 2y - 1 = 18
2x - y + 4 = 12
3x + 2y = 18 + 1
2x - y = 12 - 4
3x + 2y = 19
2x - y = 8 | * 2
3x + 2y = 19
4x - 2y = 16
dodajemy równania
3x+ 4x + 2y - 2y = 19 + 16
7x = 35
x = 35/7 = 5
2x - y = 8
2 * 5 - y = 8
10 - y = 8
- y = 8 - 10
- y = - 2
y = 2
zad 3
I 1 - 3x I = 6
1 - 3x = 6 ∨ 1 - 3x = - 6
- 3x = 6 - 1 ∨ - 3x = - 6 - 1
- 3x = 5 ∨ - 3x = - 7
3x = - 5 ∨ 3x = 7
x = - 5/3 ∨ x = 7/3
x = - 1 2/3 ∨ x = 2 1/3
∨ -znaczy "lub"
zad 4
Ix - 2) < 3
x - 2 < 3 ∧ x - 2 > - 3
x < 3 + 2 ∧ x > - 3 + 2
x < 5 ∧ x > - 1
x ∈ ( - 1 , 5 )